Table of Content - - (Journal of natural sciences, life and applied sciences, 2024)
Table of Content:1. A Geographical Analysis of the Concentrations of Air Tiny Pollutants PM2.5-PM10 on Walking Paths in the City of Buraidah and Their Relationship to Road QualityDr. Haifa Ali Alkhushiban
Keywords: Journal of Natural Sciences, Life and Applied Sciences